Factors Influencing to Purchase Intention of Organic Food Consumer in Thailand - Sangboonthai, Maneerut; Koednok, Sukumarl; Rojanapaphaporn, Worraya (Arts of Management Journal, 2022)
This article aimed to 1)develop a causal relationship model on the influence of health consciousness, value recognition, and purchase intentions of organic food consumers in Thailand; 2) analyze the direct influence of health consciousness and perceived value that affects the intention to buy organic food; and 3) analyze the indirect influence of health consciousness and perceived value that affects the intention to buy organic food through the interstitial variables on attitudes towards organic food consumption behavior. Using a quantitative research model, the population was organic food consumers in Thailand aged 15-59 years who buy organic food. A multistage sampling method was used with 541 sample respondents. The analysis of structural equation modelling. The results of the structural equation and path analysis showed that the developed model was consistent with the empirical data. The model conformance index value was CMIN/DF=1.524, CFI=0.993, TLI=0.988, GFI 0.973, NFI=0.980, RMSEA=0.031, RMR=0.018, p=0.02; 2) The results of the analysis were that health consciousness, attitude toward behavior, and subjective norm had a positive direct effect influence to purchase intention statistically acceptable 0.01. Perceived value had a direct influence on organic food purchase intentions but was statistically unacceptable; 3) Health consciousness had a direct influence on attitude toward behavior but was statistically unacceptable, and perceived value had a positive direct effect influence to attitude toward behavior statistically acceptable 0.01; and 4) Health consciousness had an indirect influence on organic food purchase intentions but was statistically unacceptable and perceived value has positive indirect effect on purchase intention through the interstitial variables on attitudes towards organic food consumption behavior that was statistically acceptable 0.01.